Formulation And Evaluation Of Anti-Aging Face Spray Preparation With Ethanol Extract Of Shoe Flower (Hibiscus Rosa-Sinensis L.) And DPPH Method Antioxidant Activity Test - Syafa Nadira Ashiilah; Rafita Yuniarti; Minda Sari Lubis; Zulmai Rani (Jurnal EduHealth, 2025)
Beauty is one of the aspects pursued by women, particularly in terms of skin care. Among the skincare products commonly used by Indonesians is face spray, which offers various benefits, such as protecting against free radicals from ultraviolet rays, preventing premature aging, and addressing dry skin. Antioxidant effects are more effective when formulated in topical preparations, such as cosmetics, compared to oral administration. Hibiscus flower is a plant that contains flavonoids, which function as antioxidants capable of protecting the skin from free radical damage, moisturizing, and enhancing skin circulation. This research is experimental in nature. In this study, ethanol extract face sprays from hibiscus flowers were prepared with concentrations of 0.1%, 0.3%, 0.5%, and 0.7%. The face sprays underwent evaluations for physical quality, preference tests, irritation tests, antioxidant activity tests, and anti-aging effectiveness tests. The anti-aging effectiveness data were analyzed using SPSS with a parametric ANOVA test. Based on the physical quality evaluation, the best formulation was the face spray with a 0.5% extract concentration. It exhibited stable organoleptic characteristics, a pH within the skin’s range of 5–7.26, good spreadability, no coarse particles or clumps, and stability during a 28-day stability test at room temperature (25°C) and a cycling test over 6 cycles. Moreover, it did not irritate the skin. The antioxidant activity test revealed that face sprays with 0.1% and 0.3% extract concentrations showed moderate antioxidant activity, while those with 0.5% and 0.7% concentrations demonstrated strong antioxidant activity. In the anti-aging effectiveness test, all formulations exhibited anti-aging effects.